Osteoarthritis and type 2 diabetes mellitus: What are the links?. (December 2016) - Courties, Alice; Sellam, Jérémie
Abstract: Osteoarthritis (OA) is the most frequent joint disorder and one of the leading cause of disability. During a long time, it was considered as the consequence of aging and mechanical stress on cartilage. Recent advances in the knowledge of OA have highlighted that it is a whole joint disease with early modifications of synovium and subchondral bone but also that it is associated with obesity and metabolic syndrome through systemic mechanisms. In the past year, type 2 diabetes has been described in two meta-analyzes as an independent risk factor for OA. In vivo models of diabetes corroborated epidemiological studies. Indeed, diabetic rodents display a spontaneous and a more severe experimental OA than their non-diabetic counterparts, which can be partially prevented by diabetes treatment (insulin, pioglitazone). The negative impact of diabetes on joints could be explain by the induction of oxidative stress and pro-inflammatory cytokines but also by advanced age products accumulation in joint tissues exposed to chronic high glucose concentration. Insulin resistance might also impair joint tissue because of a local insulin resistance of diabetic synovial membrane but also by the systemic low grade inflammation state related to obesity and insulin resistant state.